Noncontact ultrasonics used for impact damage detection on long-term water-immersed GFRP composites. (18th September 2009) - Berketis, K.; Tzetzis, D.; Hogg, P.J.
Traditional water immersion and noncontact ultrasonic C-Scan systems were used for damage detection and quantification on wet Glass Fibre Reinforced Polymer (GFRP) composite plates. Long-term immersion for up to 24 months of low-velocity impact-damaged GFRP plates in hot water at 65°C and 93°C caused serious matrix and interface degradation. The water diffusion profile was followed by water uptake measurements. The use of water-immersion, single-probe pulse-echo ultrasonics proved ineffective after long-term water immersion as damaged areas became ultrasound-invisible. The impact-damaged part was filled with water, thus acting in a similar way to the rest of the undamaged material. The use of a pair of 400 kHz air-coupled through thickness ultrasonic probes was investigated for damage detection and evaluation. The contrast between impact-damaged areas and water-diffused areas was restored and damage size detection was possible. Calibrating the system for the group wave velocity of a dry-condition specimen, a good qualitative and quantitative indication of the degraded state of specimens can be obtained. This system proved to be very promising for both the impact damage sizing and for the monitoring of the degradation process.